2007
DOI: 10.1115/1.2804620
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration of Conductive Thermal Storage Composites Made of Phase Change Materials and Graphite for Solar Plant

Abstract: New thermal storage composites made of graphite and PCM (NaNO3∕KNO3 eutectic) have been developed for solar thermal power plants using direct solar steam generation. Those materials, obtained using different elaboration routes (compounding, infiltration, cold compression) and graphite types, are presented with their respective properties (enhanced thermal conductivities, thermal storage capacities, stability) and compared together. Both the laboratory and industrial scales and grades are considered and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 6 publications
0
43
0
1
Order By: Relevance
“…Different approaches have been proposed to overcome this problem: use of metal thin strips (Hoogendoorn and Bart, 1992), thin walled rings (Velraj et al 1999), porous metals (Weaver and Viskanta, 1986) porous graphite (Tayeb, 1996), metal foam matrix (Calmidi and Mahajan, 1999) and carbon fibers (Fukai et al 2000 and are among the common techniques used to enhance the effective thermal conductivity of PCMs. The presence of the nanoparticles in the PCM increases significantly the effective thermal conductivity of the fluid and consequently enhances the heat transfer characteristics (Cabeza et al , 2002;Mettawee, and Assassa, 2007;Khodadadi, and Hosseinizadeh, 2007;Zeng et al 2007;Pincemin et al, 2008;Kim and Drzal, 2009;Ho and Gao, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been proposed to overcome this problem: use of metal thin strips (Hoogendoorn and Bart, 1992), thin walled rings (Velraj et al 1999), porous metals (Weaver and Viskanta, 1986) porous graphite (Tayeb, 1996), metal foam matrix (Calmidi and Mahajan, 1999) and carbon fibers (Fukai et al 2000 and are among the common techniques used to enhance the effective thermal conductivity of PCMs. The presence of the nanoparticles in the PCM increases significantly the effective thermal conductivity of the fluid and consequently enhances the heat transfer characteristics (Cabeza et al , 2002;Mettawee, and Assassa, 2007;Khodadadi, and Hosseinizadeh, 2007;Zeng et al 2007;Pincemin et al, 2008;Kim and Drzal, 2009;Ho and Gao, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…LHS has been widely applied in building materials, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] free cooling, [19][20][21][22] electronics cooling, [23][24][25][26][27][28][29][30][31][32][33][34] solar water heating, [35][36][37][38][39][40][41][42] solar power generation, [43][44][45][46][47][48][49] and waste heat utilization. [50][51][52][53][54]…”
Section: Technology Of Latent Heat Storage For High Temperature Applimentioning
confidence: 99%
“…as PCM and expanded graphite by Pincemin, et al [45] and Steinmann, et al [49]. Pincemin et al [43] result showed that a composite with 20% ENG has a radial thermal conductivity of 40 W/mK and 22 W/mK at 47 o C and 200 o C respectively.…”
Section: Composite Materials (Micro Encapsulation)mentioning
confidence: 99%
“…• Cold compression involves compressing a mixture of the solid PCM with the high thermal conductivity material powder at ambient temperature to form a solid composite. This method do not require thermal energy during production and there is no corrosion of equipment [45].…”
Section: Composite Materials (Micro Encapsulation)mentioning
confidence: 99%
See 1 more Smart Citation